Water and Collective Action - Meinzen-Dick, Ruth S.; Pradesh, Andhra (2022)
Ruth Meinzen-Dick Meinzen-Dick, R. 2022. Water and Collective Action. PowerPoint presentation given during the Annual Workshop of the Scaling Up Experiential Learning Tools for Sustainable Water Governance in India project, Horsley Hills, Andhra Pradesh, India, October 17-20, 2022.